Promoting strategic learning approach for Pre-University students in mathematics - Tang, Eng Loong * (2019)
In many school settings, direct instruction by teachers could be the sole instructional feature to promote the mastery of strategies and to gain knowledge. However, direct instruction could not promote transfer of strategies across contexts and time. It also restricts opportunity to activate metacognition and to employ effective use of strategies. The study attempts to overcome these deficiencies by engaging in a series of instructional activities, which involve interaction between students and the instructor, role of students and questions asked by the instructor. The initial result shows that students employ more flexible strategies, have higher level of motivation, are much independent in solving a task and are better in communicating mathematical ideas at the end of the study